Enabling gender and social inclusion in climate and agriculture policy and planning through foresight processes: assessing challenges and leverage points - Marty, Edwige; Segnon, Alcade C; Homann-Kee Tui, Sabine; Chesterman, Sabrina; Huyer, Sophia; Cramer, Laura K.; Mapedza, Everisto D. (Informa UK Limited, 2024)
Scenario-guided foresight processes are increasingly used to engage a broad range of stakeholders in sharing knowledge, reflecting, and setting priorities to respond to present and future dynamics and inform agricultural policies and planning in the face of a variable and changing climate. Such participatory approaches are key to integrating multiple expertise, perspectives and viewpoints and ensuring that the multifaceted vulnerabilities and development needs of diverse groups are addressed. However, in practice, ensuring meaningful participation is far from straightforward. In this paper, we examine the integration of gender and social inclusion considerations in fifteen scenario-guided foresight use cases across Africa, Latin America and Southeast Asia. We use key informant interviews with scenario process coordinators and a gender and social inclusion expert who participated in the workshops, as well as a review of associated reports and outputs, to unpack the ways gender and social inclusion dynamics were considered and integrated at different stages. The results suggest that few scenario-guided processes centred gender and social inclusion considerations from an early stage and consistently throughout, translating often into low diversity of stakeholders and insufficient depth reached in the produced content. Common challenges reported include time, budget, and human resources constraints as well as existing power and institutional dynamics with for instance, low women representation in technical organizations or important hierarchical social norms structuring discussions. While the focus on the future can disrupt established modes of doing, the complexity of foresight methods can also undermine effective participation leading to important trade-offs. Innovations in the modes of engagement and parallel processes with diverse groups can be important leverage points for inclusion.